Local Mediterranean food plants and nutraceuticals - Heinrich, Michael 1957-; Müller, Walter E. 1947-; Galli, Claudio (Forum of nutrition, 2006)
As a result of domestication – considered to be the most important cultural development of the past 13,000 years of human history – we depend today on a tiny number of domesticated plant and animal species for our food supply. Nevertheless, people continue to gather food which grows around their homes or they cultivate local varieties of food plants (as well as keep land races of domestic animals). Generally, wild varieties tend to be richer in micronutrients and bioactive secondary metabolites, which are produced in adaptation to local environmental conditions. These metabolites trigger further adaptive responses by producing ‘protective’, bioactive compounds which, when ingested, result in the transfer of protective effects to our organism.The preservation of local knowledge for future generations as well as the identification of new nutraceuticals by means of characterizing plant extracts with potential health beneficial effects are the main objectives of this book. The first part therefore focuses on the ethnobotanical study of local food plants in selected regions of the Mediterranean, i.e. their use as well as beliefs and cultural practices associated with it. The biological-pharmacological effects of these plants on selected (mostly in vitro) targets of the central nervous system and the cardiovascular system make up the second part, highlighting the potential of these plants for developing novel health foods, herbal medicines or local products with beneficial effects on health.Those interested in an integrated approach to the identification of new and health beneficial foods will undoubtedly find this book a valuable source of information and an inspiration for new scientific approaches to this age-old topic